The state innovation policy in the world: the goals and implementation mechanisms (Journal of Economic Research & Business Administration, 2016)
The authors reviewed the experience of state regulation of innovation policy of the leading countries in innovation development. Are given the tools and implementation methods of state regulation of innovation. There are three types of state regulation of innovation. Experience in Finland is of great importance, since it is a kind of pioneer in the development of the national innovation system integrates a science and production. In addition, interested in the experience of innovative development of South Korea and India. The analysis of the experience of the formation and de-velopment of innovative systems and implementation of innovation policy in different countries of public policy. Determined by the government's measures, which have been crucial to leap in innovation. The State must develop and implement a strategy aimed at ensuring the quality of eco-nomic growth.
Keywords: Innovational activity; state innovation policy; government regulation; foreign experience of innovative development